Job Satisfaction and Performance of Micro Finance Institutions - Dahal Chhetri, Ashmita (Madhyabindu Journal, 2025)
Job satisfaction plays a crucial role in determining employee performance, which directly influences the effectiveness and sustainability of Microfinance Institutions (MFIs). In developing economies like Nepal, MFIs rely heavily on a motivated workforce to drive financial inclusion and economic empowerment. This study aims to examine the factors affecting job satisfaction in the microfinance sector and analyze how these factors impact employee performance and overall institutional efficiency. The study employs a descriptive and causal-comparative research design, collecting primary data from 119 employees working in six MFIs in Chitwan District, Nepal. A structured questionnaire was used to gather data, ensuring reliability through a pilot test (Cronbach’s Alpha = 0.78). Purposive sampling was applied to include employees from diverse backgrounds. Statistical analysis was conducted using SPSS version 25, incorporating descriptive statistics (mean, standard deviation) and inferential techniques (correlation and regression analysis) to identify key relationships. Findings reveal that reward and benefit structures significantly influence job satisfaction, followed by workplace relations and career development opportunities. However, gender disparities and varying employee perceptions highlight the need for targeted interventions. The study emphasizes the importance of enhancing compensation, promoting career growth, and fostering a supportive work environment to improve job satisfaction and, consequently, MFI performance. These insights provide valuable recommendations for HR policies in Nepal’s microfinance sector, contributing to employee well-being and long-term organizational success